Understanding the engagement and consequences of user generated online video and its virality towards generation y political inclination / Wan Hartini Wan Zainodin - Wan Zainodin, Wan Hartini (2018)
This qualitative study focuses the engagement and consequences of user generated online video and its virality towards Gen Y political inclination. To gain insights on the central focus of this study, six research questions were addressed : (1) Why Gen Y are utilizing the User-generated online video in understanding the state political scenario?, (2) How does virality of User-generated online video contributes to voting decision among Gen Y?, 3) How does the User-generated online video and its virality contribute to the perception of Gen Y towards the Federal Government ruling parties?, (4) How does User-generated online video and its virality contribute to the perception of Gen Y towards the opposition parties?, (5) How does User-generated online video and its virality contribute to the perception of Gen Y towards the Federal Government ruling politicians?, and (6) How does User-generated online video and its virality contribute to the perception of Gen Y towards opposition politicians? This study was guided with three theories; (i) Uses and Gratifications Theory, (ii) Media System Independency Theory and Standpoint Theory. Using phenomenology approach, salient discoveries were obtained through in-depth interviews with 15 User Generated Online Video (UGOV) User residing in Klang Valley. Data analysis was conducted simultaneously with data collection and the NVivo 11.0 software was used in the process of coding. Thematic analysis and constant comparison strategy were used to analyse the data. It was disclosed that UGOV platform such as YouTube must also be considered important for the political parties and the politicians. The power of audio video that this medium owned has become an alternative option which also has breaking the dominance of conventional mainstream media. UGOV platforms as well as other social media platform must be taken seriously as a platform that will spread government agenda and explanation especially when it comes to the issues that bothers Gen Y. The shifting from conventional mainstream to social media platform have send strong message to the mainstream media to change the way political issues being reported. In overall, this study had managed to observed UGOV platform that is YouTube as among of the social media sites that have become powerful brands. Despite the complexity and flexibility of UGOV, this medium has offered the Gen Y new opportunities to present their viewpoints directly to the key constitution. Thus, the findings reveal that UGOV reinforces potential impact in shaping the Gen Y political attitudes and behavior. From the perspective of UGOV Users Gen Y preferred to be empowered and engaged rather than being subtly directed and forced to accept on the matters that they cannot validate and rely on.